Pregunta
\( =-p+10 p^{2} \) and \( C=2 p+7 \), find an expression that equals \( B+3 C \) dard form.
Ask by Carrillo Lang. in the United States
Feb 04,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The expression \( B + 3C \) in standard form is \( 10p^{2} + 5p + 21 \).
Solución
To find an expression that equals \( B + 3C \) given the equations:
\[
B = -p + 10p^{2}
\]
\[
C = 2p + 7
\]
Follow these steps:
1. **Express \( 3C \):**
\[
3C = 3(2p + 7) = 6p + 21
\]
2. **Add \( B \) and \( 3C \):**
\[
B + 3C = (-p + 10p^{2}) + (6p + 21)
\]
3. **Combine like terms:**
\[
B + 3C = 10p^{2} + (-p + 6p) + 21 = 10p^{2} + 5p + 21
\]
So, the expression that equals \( B + 3C \) in standard form is:
\[
10p^{2} + 5p + 21
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find an expression that equals \( B + 3C \), we first need to substitute the original expressions for \( B \) and \( C \). We have: \( B = -p + 10p^{2} \) \( C = 2p + 7 \) Now, we can calculate \( 3C \): \[ 3C = 3(2p + 7) = 6p + 21 \] Next, we add \( B \) and \( 3C \): \[ B + 3C = (-p + 10p^{2}) + (6p + 21) \] Combining like terms: \[ B + 3C = 10p^{2} + (-p + 6p) + 21 \] \[ = 10p^{2} + 5p + 21 \] So, the expression that equals \( B + 3C \) in standard form is: \[ 10p^{2} + 5p + 21 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium